GRIP STRENGTH: EFFECT OF GENDER AND HAND DOMINANCE - Nurgül Arıncı İncel,; Esma Ceceli,; Pınar Bakıcı Durukan,; Öznur Öken,; H. Rana Erdem, (Archives of Rheumatology, 2002)
Grip strength provides an objective index for the functional integrity of upper extremity. Aim of this study was to investigate the differences between gender for hand grip stength and to evaluate grip strengths of right and left handed male and female participants. There was statistically significant difference between grip strengths of dominant and nondominant hands in favor of the dominant hand for the whole group. Besides, men were found to be stronger for both dominant and nondominant sides. 13.23% of male and 8.33 % of female right handed participants had stronger nondominant grips. The percentage of stronger nondominant hands for left handed men (46.15%) was significantly higher than left handed women (12.5%). We concluded that the hypothesis of left handed people having stronger nondonminant hands than right handed people cannot be generalized.